Tensions and Paradoxes in Creativity and Innovation - Kristina Potonik; Bart Verwaeren; Bernard Nijstad (Journal of Work and Organizational Psychology, 2022)

(untitled)
Most often understood as the generation of novel and useful ideas and their implementation, research on creativity and innovation has mushroomed in recent years. Although these studies provided useful insights into how organizations can enhance both phenomena, there is a growing consensus in the literature suggesting that rather than inherently beneficial, creativity and innovation are in fact ripe with tensions and competing demands. These tensions may put individuals and teams under pressure as they try to a) come up with novel, but also useful and implementable ideas, b) complete their core tasks efficiently, but also suggest novel and useful ideas for their improvement, and c) bring uniqueness to the table, but at the same time form cohesive collectives. In this integrative review, we illustrate these tensions with research evidence and provide recommendations about how we can manage them in order to benefit from individual and team creative and innovative efforts.